BSA - loaded gelatin microspheres: Comparative studies on biodegradation and drug release in presence of collagenase and trypsin - Kristina Mladenovska; Emilija Janevic; Marija Glavas-Dodov; Renata Slavevska-Raicki; Maja Simonoska; Katerina Goracinova (University Ss Cyril and Methodius in Skopje, Faculty of Pharmacy and Macedonian Pharmaceutical Association, 2003)
Certain variations in the process parameters (emulsification time, surfactant concentration) were performed in order to prepare BSA-loaded gelatin microspheres with particle size ranging from 1 to 10 µm and high loading efficiency using a procedure originally employed by Tabata and Ikada. In vitro degradation and drug release studies in the presence of trypsin and collagenase, respectively, were performed in order to evaluate the potential of gelatin microspheres as regulated and sustained release systems for oral vaccination. Degradation data showed that the preparation procedure had provided prolonged degradation in the presence of both enzymes, suggesting complete in vivo degradation. Exponential dependence of the amount of drug released on time was evidenced. The diffusion coefficients were superior to 0.5 indicating the Case II anomalous Fickian diffusion, except for the particles smaller than 5 µm where in the presence of collagenase the transition to Super Case II transport was observed due to the higher rate of polymer degradation and BSA diffusion through the matrix. The mathematical modeling of drug release showed a biphasic release pattern in the presence of both enzymes, where the rate constants for the initial time release confirmed the influence of the particle size and/or enzymatic degradation rate on the drug release rate.